Improving treatment outcomes for Graves’ disease patients with inactive forms of Graves’ orbitopathy through an increased dose of radioiodine therapy - Gosmann, Janika; Willms, Diana; Bell, Eberhard; Schreckenberger, Mathias; Willms, Arnulf (Nuklearmedizin - NuclearMedicine, 2020)
Introduction While surgical treatment is preferred for Graves’ disease with active forms of GO, there are various concepts for treating inactive forms of GO. The goal of radioiodine therapy is to resolve immunogenic hyperthyroidism by damaging the thyroid cells.The effects of the radioiodine dose on an associated inactive GO remain unclear, however.Methodology We conducted a retrospective analysis of 536 patients who received first-time radioiodine therapy to treat Graves’ hyperthyroidism. Patients without GO always received 200 Gy of iodine-131. Before the introduction of a differentiated treatment concept, patients with GO also received 200 Gy, while afterwards they received 300 Gy. For further analysis, we formed three patient groups based on GO diagnosis and administered radiation dose and compared their results. The main research question focused on the effect of an increased dose on Graves’ orbitopathy. The sub-questions addressed the resolution rate achieved with the higher dose as well as the development of GO in patients who received radioiodine therapy.Results The results show that GO symptoms were improved after radioiodine treatment in 68.5 % of patients treated with 300 Gy but only in 47.5 % of the patients treated with 200 Gy (p = 0.003). While in the 300 Gy group, hyperthyroidism was resolved in 93.2 % of patients, this was achieved in only 68.8 % of patients in the 200 Gy group (p </= 0.001).Discussion Especially with an inactive form of GO profit from their hyperthyroidism being quickly and sufficiently resolved. This is achieved significantly better by administering 300 Gy instead of 200 Gy. For this reason, data analysis supports a differentiated dose concept that provides 300 Gy for patients with GO and 200 Gy for patients without GO.
Keywords: Graves’ disease; radioiodine therapy; thyroid eye disease; Graves’ orbitophy